Epicardial adipose tissue thickness in type 1 diabetic patients - ÖZBEN SADIÇ, BESTE; YAVUZ, DİLEK; ÜSTAY, ÖZLEM (SPRINGER, 2011)
Insulin resistance is getting important in the course of type 1 diabetes mellitus. Visceral fat depot is associated with insulin resistance and assessment of epicardial fat thickness is a way of measuring visceral fat. The aim of the study was to measure epicardial adipose tissue (EAT) thickness and to determine its relationship with waist-hip-ratio (WHR) and estimated glucose disposal rate (eGDR) in adult type 1 diabetic patients. Thirty-six type 1 diabetic patients (aged 31 +/- 8 years; Female/Male: 22/14) and 43 age, gender and BMI matched healthy controls were included. Fasting blood glucose (FBG), hemoglobin A1c, and lipid profiles were measured. Waist-hip-ratio (WHR) was calculated. Daily insulin dose/kg of patients were recorded and eGDR of all subjects was calculated. Epicardial adipose tissue (EAT) thickness was evaluated by echocardiography. EAT thickness of the type 1 diabetic patients was significantly higher than controls (3.30 +/- 1.06 vs. 2.30 +/- 0.34 mm, P < 0.0001). EAT thickness was correlated with age (P = 0.05; r = 0.35), WHR (P = 0.003; r = 0.67), daily insulin dose/kg (r = 0.45, P = 0.005), and eGDR (r = -0.55, P = 0.0004). Multivariate analysis revealed WHR and eGDR to be related to EAT among age, WHR, daily insulin dose/kg, eGDR, FBG, and hemoglobin A1c (r(2) of the model = 0.64). Epicardial adipose tissue thickness is increased in type 1 diabetic patients compared to controls and is related to WHR and eGDR in this group of patients. This measurement may point to the presence of insulin resistance in type 1 diabetic patients.
Keywords: Epicardial adipose tissue thickness; Type 1 diabetes mellitus; Insulin resistance; Estimated glucose disposal rate; CARDIOVASCULAR RISK-FACTORS; CORONARY-HEART-DISEASE; METABOLIC SYNDROME; INSULIN-RESISTANCE; PITTSBURGH EPIDEMIOLOGY; FAT; COMPLICATIONS; SEVERITY; ECHOCARDIOGRAPHY; ASSOCIATION